Spruce milled wood lignin: linear, branched or cross-linked? - Balakshin, Mikhail; Capanema, Ewellyn Augsten; Zhu, Xuhai; Sulaeva, Irina; Potthast, Antje; Rosenau, Thomas; Rojas, Orlando J (Green chemistry : an international journal and green chemistry resource : GC, 2020)
The subject of lignin structure, critical for fundamental and practical reasons, is addressed in this study that includes a review of the methods applied to elucidate macromolecular branching. The recently available approaches for determination of the absolute molecular mass of spruce milled wood lignin (MWL) along with the quantification of terminal groups clearly indicate that MWL is significantly branched and cross-linked (with ∼36% lignin units partaking in these linkages). Results from independent methods imply that about half of the branching and crosslinking linkages involve aromatic rings, predominantly 5-5′ etherified units; meanwhile, a significant number of linkages are located in the side chains. Quantitative 13 C NMR analyses suggest that the branches involve different aliphatic ether (alkyl-O-alkyl) types at the α- and γ-positions of the side chain, with intact β-O-4 linkages. While the exact structures of these moieties require further investigation, our results point to the fact that conventional lignification theory disagrees with the presence of such key moieties in softwood MWL and the observed high degree of branching/crosslinking. Potential reasons for the noted discrepancies are discussed. Plausible up-to-date structural model of spruce MWL in agreement with the current structural and molecular weight data.